Pengaruh Harga, Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor Yamaha N-Max Di PT.Alfa Scorpii SM Raja Medan - Mailani Mailani; Yahya Tanjung (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Purchasing decision is a form of consumer behavior in using a product. Purchasing targets will be a chieved if the purchasepusher attributes are fulfilled by the company, one ofthese attributes, namely price, promotion and product quality. The analysis used includes validity test, reliability test, classical assumption test, multiple liniear analysis test and the coefficient of determination. The results of this study indicate that partially price has a positive and significant effect on purchasing decisions, promotion has a positive and significant, effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions and simultaneously the variables of price, promotion and product quality have a positive and significanet effect on purchasing decisions basedon the R square value of 0.755 which canbe called the coefficient of determination which in this case means 755% while the rest is expllained by other factors such as brand image, product design, brand image, economic conditions and consumer tastes.